Balloon cell melanoma: a systematic review. (1st March 2021) - Wei, Grace; Hennessy, Kerry; Kevin Heard, L.; Gaudi, Sudeep; Mhaskar, Rahul; Patel, Rishi R.; Bennett, Adam E.
Abstract: Balloon cell melanoma (BCM) is a rare presentation of malignant melanoma characterized by large, foamy melanocytes lacking pigmentation. This is a comprehensive review of the clinical, dermoscopic, and histological features among BCM cases reported in the literature. A systematic review of all case reports and series published since 1970 was conducted via MEDLINE, Embase, and Web of Science, using "balloon cell melanoma" and synonymous search terms. Our systematic search identified 76 cases (49% male, 51% female) of BCM in the literature. The mean age at presentation was 57.81 years. Prior skin cancer, particularly melanoma (47%), accounted for 58% of pertinent medical history. Prominent clinical exam findings included raised (46%), ulcerated (73%) lesions larger than 1 cm (68%) in the lower extremities (35%). Median Breslow thickness of primary BCM cases was 2.5 mm. Hairpin vessels (75%) and structureless architecture (75%) were predominant on dermoscopy. Notable histopathology included large (47%), vacuolated (58%) cells with foamy cytoplasm (62%) and conspicuous nucleoli (27%). Positive S‐100 immunohistochemistry (73%) was most frequently employed to diagnose BCM. We observed 47% primary and 53% metastatic BCM cases. Of metastatic BCMs, balloon cells in the primary lesion were unknown in 48%, devoid in 33%, and present in 20% of cases. All metastases displayed predominant balloon cell morphology. BCM may represent an advanced phase in the progression of malignant melanoma. Improved awareness of BCM characteristics among clinicians may reduce the risk of misdiagnoses.